The development and validation of an UV-Vis spectrophotometric method for the determination of ciprofloxacin in raw material and dosage forms - Timothé Mavanga Mabaya; Jocelyn Mankulu Kakumba; Mannix Mayangi Makola; Adelard Mbenza Puati; Didi Mana Kialengila; Jean Mavar Tayey Mbay; Jeremie Mbinze (Orapuh Journal)
Introduction